PENINGKATAN HASIL BELAJAR BIOLOGI MENGGUNAKAN METODE SQ3R PADA PESERTA DIDIK KELAS XI IPA 1 MAN 5 JAKARTA - Erdawati Erdawati (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2022)
Abstract This study aims to improve students' biology learning outcomes by applying the SQ3R method to students in class XI IPA 1 MAN 5 Jakarta in the academic year. This type of research is classroom action research with a research design using Kurt Lewin's model. The researcher conducted the research in semester 1 (odd) of the 2019/2020 school year. The research subjects were students of class XI IPA 1 MAN 5 Jakarta, which consisted of 30 students. The object of research was the learning outcomes of students' biology. Data collection techniques used observation and interviews. The research data were analyzed descriptively and presented in tables and graphs. The results showed an increase in students' biology learning outcomes; in the first cycle, the average class score was 72.83 with learning mastery at only 26.67%, then in the second cycle, it increased to 83.00 with learning mastery reaching 93.33%. There is an increase in student learning activities. Students are more enthusiastic about taking lessons; students' ability to ask questions is getting better; students are active in finding learning resources; students are active in discussion and fluent in answering questions. Based on the study results, the conclusion is that applying the SQ3R method in Biology subjects can improve students' learning outcomes and learning activities in class XI IPA 1 MAN 5 Jakarta.   Abstrak Tujuan penelitian ini yaitu meningkatkan hasil belajar biologi peserta didik melalui metode SQ3R di MAN 5 Jakarta. Jenis penelitian yaitu tindakan kelas (PTK), dengan desain model Kurt Lewin. Penelitimelakukan penelitian pada semester 1 tahun pelajaran 2019/2020. Subyek penelitian yaitu peserta didik kelas XI IPA 1 MAN 5 Jakarta yang terdiri dari 30 orang. Objek penelitian adalah hasil belajar biologi. Data penelitian dilakukan dengan teknik observasi serta wawancara. Data penelitian dianalisis secara deskriptif kemudian ditampilkan dalam tabel dan grafik. Hasil penelitian menunjukkan terjadinyapeningkatan hasil belajar biologi setiap siklus. Nilai rata-rata kelas pada siklus I yakni 72,83 dengan ketuntasan belajar hanya 26,67%, kemudian meningkat menjadi 83,00 pada siklus II dengan ketuntasanbelajar mencapai 93,33%. Terdapat peningkatan aktivitas belajar siswa. Siswa lebih antusias mengikuti pelajaran; kemampuan siswa dalam bertanya menjadi semakin baik; siswa aktif dalam mencari sumberbelajar; siswa aktif dalam berdiskusi dan lancar dalam menjawab pertanyaan. Berdasarkan hasil penelitian, penerapan metode SQ3R pada pelajaran Biologi dapat meningkatkan hasil serta aktivitas belajarpeserta didik kelas XI IPA 1 MAN 5 Jakarta.